2004
DOI: 10.1159/000081887
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Basal Inner Ear Structures in Cochlear Implantation

Abstract: The aim of this report was to examine basal trauma in implanted human temporal bones and discuss modified approaches to the basal cochlear turn to avoid destruction of basal cochlear structures. Thirty-three human temporal bones were implanted with four different cochlear implant electrode arrays manufactured by MED-EL using either a caudal approach cochleostomy or round window membrane insertions. All specimens were processed with a special histological technique that allows sectioning of undecalcified bone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 30 publications
2
58
0
3
Order By: Relevance
“…These data support the results of Adunka et al, 14 who showed, in 2004, that cochleostomy has a higher risk of destructive basal trauma (48%) compared with performing round window membrane insertions (15%). In all cases, the electrode array penetrated the basal membrane in the first 45°segment of the cochlea.…”
Section: Discussionsupporting
confidence: 91%
“…These data support the results of Adunka et al, 14 who showed, in 2004, that cochleostomy has a higher risk of destructive basal trauma (48%) compared with performing round window membrane insertions (15%). In all cases, the electrode array penetrated the basal membrane in the first 45°segment of the cochlea.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies and discussion in the literature have identified the potential for damage to the spiral ligament, basilar membrane and osseous spiral lamina occurring due to the creation of the cochleostomy [Briggs et al, , 2005Adunka et al, 2004]. If the cochleostomy is sited anterior, rather than inferior, to the RWM, there is the distinct possibility of significant trauma to the adjacent basal turn structures making successful hearing preservation less likely.…”
Section: Discussionmentioning
confidence: 99%
“…In a large series of human cadaver temporal bone experiments, we were able to demonstrate atraumatic electrode insertions with the MED-EL device [Adunka et al, 2004a]. In those cases, the array was found to be sliding along the inferior part of the lateral wall of the scala tympani.…”
Section: Surgical Proceduresmentioning
confidence: 93%